Erenumab (AMG 334) in episodic migraine: Interim analysis of an ongoing open-label study. (19th September 2017) - Ashina, Messoud; Dodick, David; Goadsby, Peter J.; Reuter, Uwe; Silberstein, Stephen; Zhang, Feng; Gage, Julia R.; Cheng, Sunfa; Mikol, Daniel D.; Lenz, Robert A.
Abstract : Objective: To assess long-term safety and efficacy of anti–calcitonin gene-related peptide receptor erenumab in patients with episodic migraine (EM). Methods: Patients enrolled in a 12-week, double-blind, placebo-controlled clinical trial (NCT01952574) who continued in an open-label extension (OLE) study will receive erenumab 70 mg every 4 weeks for up to 5 years. This preplanned interim analysis, conducted after all participants had completed the 1-year open-label follow-up, evaluated changes in monthly migraine days (MMD), achievement of ≥50%, ≥75%, and 100% reductions, Headache Impact Test (HIT-6) score, Migraine-Specific Quality of Life (MSQ), Migraine Disability Assessment (MIDAS), and safety. Data reported as observed without imputation for missing data. Results: Of 472 patients enrolled in the parent study, 383 continued in the OLE with a median exposure to erenumab of 575 days (range 28–822 days). Mean (SD) MMD were 8.8 (2.6) at parent study baseline, 6.3 (4.2) at week 12 (beginning of OLE), and 3.7 (4.0) at week 64 (mean change from baseline [reduction] of 5.0 days). At week 64, 65%, 42%, and 26% achieved ≥50%, ≥75%, and 100% reduction in MMD, respectively. Mean HIT-6 scores were 60.2 (6.3) at baseline and 51.7 (9.2) at week 64. MSQ and MIDAS improvements from baseline were maintained through week 64. Safety profiles during the OLE were similar to those in the double-blind phase, which overall were similar to placebo. Conclusions: One-year efficacy, supported by functional improvements and favorable safety and tolerability profiles, supports further investigation of erenumab as a preventive treatment in patients with EM. Clinicaltrials.gov identifier: NCT01952574. Classification of evidence: This study provides Class IV evidence that for patients with episodic migraine, erenumab reduces long-term MMD and improves headache-related disability and migraine-specific quality of life.